Pengelolaan Hutan Bersama Multistakeholder Sebagai Pelaksanaan Corporate Social Responcibility (CSR) - Rosmaladewi, Okke; Danuwikarsa, Ibrahim; Pranadikusumah, Panji (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
The conversion of protected forest areas into horticultural crops occurs rapidly and massively in the upstream areas. This causes environmental damage, environmental pollution and natural disaster such as landslides and forest fires. With the declining carrying capacity of the forest resources,comprehensive, participatory and sustainable forest management system with a partnership approach, economic development, environmental sustainability and stakeholder involvement is required. Multistakeholder forest management is an alternative to reducethe over forest area functions and the risk of natural disasters. The integrated programs are initiated from the inventory of natural and forest resources, mapping the socio-economic of forest villagers conditions, joint planning of forest area management by involving stakeholders, implementing environmental awareness programs,rehabilitation and conservation on overcommodities and location. Technical and social assistance, monitoring and evaluation are done jointly and periodically. All is executed to restore the function of forest area into sustainable forest and disaster alert.